Перспективи використання газових інфрачервоних нагрівачів у теплотехнологічних процесах - Шпак, Григорій; Лозбін, Віктор (Видавництво Національного університету «Львівська політехніка», 2001)
The possibilities of the use of the gas infrared heaters in thermaltechnological processes have been considered in the article. The example of the installation for the formation of polyethylene articles shows the advantages of gas infrared heaters before another methods of heating in small batch manufacturing.